ESTIMATION OF THE WATER DEMAND OF THE IRRIGATED SUGARCANE USING REMOTE SENSING - Oliveira, DANIELA ARAÚJO DE [UNESP] (2021)
This work aimed to estimate the water demands of the sugarcane crop irrigated by the central pivot system, through the application of the SAFER (Simple Algorithm for Evapotranspiration Retrieving) algorithm. The study was conducted in a commercial area, in the city of Nova Independência, SP, comprising the 2020/21 harvest. Images from the Landsat 8 and Sentinel 2 satellites and agrometeorological data were used to estimate the ETa/ETo ratio and actual evapotranspiration (ETa). The highest values of ETa observed were between 3.4 and 4.4 mm day-1, while the highest values of the ETa/ETo ratio were 0.7 and 0.8, and despite similar behavior to similar works, they are smaller than those indicated in the literature.